Double Discretization Difference Schemes for Partial Integrodifferential Option Pricing Jump Diffusion Models - M.-C. Casabán; R. Company; L. Jódar; J.-V. Romero (Abstract and Applied Analysis)
A new discretization strategy is introduced for the numerical solution of partial integrodifferential equations appearing in option pricing jump diffusion models. In order to consider the unknown behaviour of the solution in the unbounded part of the spatial domain, a double discretization is proposed. Stability, consistency, and positivity of the resulting explicit scheme are analyzed. Advantages of the method are illustrated with several examples.